STRATEGI MEDIA SOSIAL KANG DEDI MULYADI (KDM): CITRA DAN RESPON MASYARAKAT JAWA BARAT - Agus Setiaman; Naufal Rifqi Ananda (Jurnal Kajian Budaya dan Humaniora, 2025)
The content displayed by Dedi Mulyadi through his social media channels is not only formal or just an elitist image. However, he also shows real action and deep social empathy. Furthermore, his political communication style shows his direction towards establishing a pro-people leadership image. This is reflected in Dedi Mulyadi's political actions, which do not limit himself to the official table or political ceremonies alone, but also act directly in the field, greeting the people with his appearance and simple language. Through this narrative, he succeeded in creating the image of a leader who is not only good at talking but also has real actions. The phenomenon of the presence of the figure of Dedi Mulyadi is interesting because his appearance comes amidst a widespread crisis of public trust in politicians who tend to distance themselves from the people. At a time when many politicians focus on image through campaign advertisements that are stiff and do not touch people's emotional side, such as through campaign boards or posters with images of faces that are bigger than their words. Dedi Mulyadi is actually present by utilizing direct communication and building emotional relationships either through face-to-face or published digital content. Through this communication style, it strengthens the perception that he is a leader who is worthy of being trusted and used as a role model, especially in a society that desires leaders who are honest, caring, and not distant.